Realising Kenya’s Artificial Intelligence Strategy - Ogot, Madara (UbuntuNet Alliance for Research and Education Networking, 2026)
The Kenya Artificial Intelligence (AI) Strategy 2025-2030 seeks to position Kenya as a leading AI hub, aligned to Kenya’s national development priorities, especially in agriculture, healthcare, education, finance and public administration. The Hierarchy of Engagement with AI model offers a practical framework for the Strategy’s implementation. The model frames engagement with AI across eight progressive maturity levels, integrating technical capability, governance, ethics, workforce, and ecosystem collaboration into a manageable, measurable stage-gated journey. Realising Kenya’s AI Strategy requires a clear evidence-based pathway that the HE-AI model provides. The model’s sequenced logic and delineation of actor roles, both aligned with the Strategy, will support its implementation.
Keywords: Artificial Intelligence; Policy; Hierarchy of Engagement With AI Model; Maturity Model; Kenya